2022
DOI: 10.1177/00027642221118265
|View full text |Cite
|
Sign up to set email alerts
|

From “Angry Mobs” to “Citizens in Anguish”: The Malleability of the Protest Paradigm in the International News Coverage of the 2021 US Capitol Attack

Abstract: This study tests the robustness of the “protest paradigm”—a routinized, predominantly negative pattern in covering social protest—by examining the news coverage of the 2021 US Capitol attack in eight countries that vary in the nature of their political regime and geopolitical standing, with democratic US allies United Kingdom, Canada, Germany, France, Australia on one side, and authoritarian adversaries Russia, China, and Iran on the other. Based on a computer-assisted analysis of 3,579 news articles, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Analyses of word choice are important. As Kananovich (2022) rightfully pointed out, the labels journalists use (e.g., protest, riot, insurrection, rally) serve as framing cues for how audiences will understand protest activity. Likewise, the words scholars use to identify news stories about protest can skew our analyses, calling into question whether or how the paradigm operates differently for radical protests or those that support or challenge power hierarchies.…”
Section: Innovating Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of word choice are important. As Kananovich (2022) rightfully pointed out, the labels journalists use (e.g., protest, riot, insurrection, rally) serve as framing cues for how audiences will understand protest activity. Likewise, the words scholars use to identify news stories about protest can skew our analyses, calling into question whether or how the paradigm operates differently for radical protests or those that support or challenge power hierarchies.…”
Section: Innovating Methodological Approachesmentioning
confidence: 99%
“…If the coverage includes protesters’ perspectives only because they align with the media organization's political or economic interests—which often are linked with the interests of political and business elites, especially in countries with polarized or instrumentalized media systems (see Harlow et al 2022)—then the debate frame becomes less about legitimizing protesters and more about maintaining social control and upholding the status quo. We thus see a need to build on the work of scholars who have used the paradigm to examine pro-status quo protests and riots (e.g., Kananovich 2022; Mourão 2021). While these studies have found that use of the debate frame and other portrayals of protesters do not necessarily follow the delegitimizing coverage patterns predicted by the paradigm, we argue that the applicability of the paradigm is less important than the analysis of power structures.…”
Section: Reimagining a More Critical Paradigmmentioning
confidence: 99%